2013
DOI: 10.1007/s13277-013-1487-3
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and immunohistochemical expression of hMLH1 and hMSH2 in sporadic colorectal cancer: a study from India

Abstract: To determine the etiological factors of human colorectal cancer (CRC) we assessed the frequency and prognostic significance of hMLH1 and hMSH2 genes in conjunction with hMLH1 and hMSH2 protein expression in 30 Indian CRC patients. The protein expression and promoter methylation of hMLH1 and hMSH2; Mismatch Repair genes (MMR) were analyzed by immunohistochemistry and methylation-specific PCR (MSP), respectively. A loss of hMLH1 expression was recognized in 4(13.3%) and loss of hMSH2 expression was recognized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…25 A recent study from north India by Dubey et al reported MSI-high in 22% patients. 26 Earlier, two studies from India by Pandey et al 27 and Malhotra et al 28 have reported MMR protein loss from 17.8-19.9%. But both had reported their study with only 2 antibodies, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…25 A recent study from north India by Dubey et al reported MSI-high in 22% patients. 26 Earlier, two studies from India by Pandey et al 27 and Malhotra et al 28 have reported MMR protein loss from 17.8-19.9%. But both had reported their study with only 2 antibodies, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…In HNSCC, 50% of tumors harbored methylation at either or both MLH1 and MSH2 promoters . Methylation of MLH1/MSH2 genes was also associated with colorectal cancers and lung cancers . In pretherapeutic BC, TNBC showed the highest deletion but in NACT‐treated samples, HER2‐enriched type showed the highest deletion hinting toward the differences in the pathogenesis of the molecular subtypes of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation in CpG islands has been demonstrated to be a novel mechanism of tumor suppressor gene silencing ( 7 , 8 ). A number of genes have now been demonstrated to be hypermethylated in colorectal tumors, including APC ( 11 ), MLH1 ( 43 ) and O 6 -methylguanine DNA methyltransferase ( 44 ). For example, the inactivation of the cyclin-dependent kinase inhibitor P16 / CDKN2A / INK4a by methylation leads to the disruption of cell-cycle regulation and potentially provides a growth advantage to affected cells ( 45 ).…”
Section: Discussionmentioning
confidence: 99%